1996
DOI: 10.1128/jb.178.8.2368-2374.1996
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyl-terminal processing of the cytoplasmic NAD-reducing hydrogenase of Alcaligenes eutrophus requires the hoxW gene product

Abstract: Two open reading frames (ORFs) were identified immediately downstream of the four structural genes for the soluble hydrogenase (SH) of Alcaligenes eutrophus H16. While a mutation in ORF2 had no obvious effect on hydrogen metabolism, an in-frame deletion in ORF1, subsequently designated hoxW, led to a complete loss of SH activity and hence a significant retardation of autotrophic growth on hydrogen. Hydrogen oxidation in the hoxW mutant was catalyzed by the second hydrogenase, a membrane-bound enzyme. Assembly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 41 publications
1
61
0
1
Order By: Relevance
“…It is anticipated that the resulting cofactor intermediate is subsequently transferred to the apo-hydrogenase (13, 18 -20). In a process assisted by the HypA and HypB proteins, nickel is inserted (21), and maturation of the active site-containing large subunit is completed through specific endoproteolytic cleavage of a C-terminal amino acid extension that triggers protein folding and the final assembly with the electron-transferring small subunit (22,23 3 spectroscopy revealed that 13 CO, externally supplied to hydrogenase-synthesizing cell cultures, is efficiently incorporated into the active site of the enzymes (12,14). Taking an average CO concentration of 0.1 ppmv (24) in the northern hemisphere into account, it is theoretically conceivable that atmospheric CO serves as the source of the carbonyl ligand.…”
mentioning
confidence: 99%
“…It is anticipated that the resulting cofactor intermediate is subsequently transferred to the apo-hydrogenase (13, 18 -20). In a process assisted by the HypA and HypB proteins, nickel is inserted (21), and maturation of the active site-containing large subunit is completed through specific endoproteolytic cleavage of a C-terminal amino acid extension that triggers protein folding and the final assembly with the electron-transferring small subunit (22,23 3 spectroscopy revealed that 13 CO, externally supplied to hydrogenase-synthesizing cell cultures, is efficiently incorporated into the active site of the enzymes (12,14). Taking an average CO concentration of 0.1 ppmv (24) in the northern hemisphere into account, it is theoretically conceivable that atmospheric CO serves as the source of the carbonyl ligand.…”
mentioning
confidence: 99%
“…Near the carboxy terminus, HoxH possesses a strongly conserved motif ending with a histidine. The formation of the mature protein and the incorporation of Ni into it might require the cleavage of a stretch of 26 amino acids behind this His similar as in the proteins from Methanococcus voltae [16], E. eoli (hydrogenase 3) [17], and A. eutrophus [18]. An N-terminal leader sequence is also not observed in HoxH of A. nidulans.…”
Section: (K) (I) (S) Vflddqgnaementioning
confidence: 99%
“…1, Table 1). A sequence for a protein with no obvious function (ORF2) resides between hoxW and hypA in A. eutrophus [18]. Such a protein is not encoded in the same region on the A. nidulans genome.…”
Section: Characterization Of Accessory Genesmentioning
confidence: 99%
See 2 more Smart Citations